Rheological measurements and structural analysis of polymeric materials - Münstedt, Helmut (Polymers, 2021)
Rheological measurements of polymer melts are widely used for quality control and the optimization of processing. Another interesting field of rheology is to provide information about molecular parameters of polymers and the structure build-up in heterogeneous polymeric systems. This paper gives an overview of the influence of molar mass, molar mass distribution and long-chain branching on various rheological characteristics and describes the analytical power following from established relations. With respect to applications, we discuss how rheological measurements can be used to gain insight into the thermal stability of a material. A special impact lies in the demonstration, how long-chain branching can be analyzed using rheological means like the zero-shear viscosity as a function of molar mass and strain hardening occurring in elongation. For contributions to branching analysis, the thermorheological behavior and activation energies are particularly discussed. The use of elastic quantities in the case of mechanical pretreatment effects is briefly addressed. The influence of fillers on recoverable properties in the linear range of deformation is analyzed and the role of their specific surface area for interactions described. It is shown how the fundamental results can be applied to study the state of nanoparticle dispersions obtained under special conditions. Furthermore, it is demonstrated that the findings on polymer/filler systems are the base of structure analyses in heterogeneous polymeric materials like polyvinylchloride (PVC) and acrylonitrile-butadiene-styrene copolymers (ABS).
CRIS-Team Scopus Importer:2021-04-23
Keywords: Analysis of branching content; Mechanical pretreatment effect; Particle-filled polymeric systems; Polymer melts; Relations with molecular parameters; Rheological behavior of heterogeneous polymers; Rheological properties; Studies of thermal stability